KAJIAN ISLAM TENTANG TERORISME DAN JIHAD - Kholid Hidaytullah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2016)
Jihad and terrorism are two terms that have always been the focus of international attention. There are some mistakes that need to be clarified, especially related to the meaning of jihad in Islam. The international community assumed that both terms-tangible into motion some activist groups that exist in the Islamic-are two sides that can not be separated. Making of war or jihad that many written by Western scholars tend to confuse terrorism with the term jihad. This was done because it may depart from hatred and lack of empathy. Especially after the attacks on the World Trade Centre (WTC) on 9 November 2001 the United States declared war against the terrorists. That term refers to a group of Al-Qaeda leader Osama bin Laden is considered a global terrorist. The issue of an increasingly globalized terrorism in Indonesia after the Bali bombing in October 12, 2012 during the Megawati administration. Map terrorism as being part of the Islamic world.